ChemInform Abstract: A Two‐Directional Approach to Pyrrolizidines: Total Syntheses and Biological Evaluation of Alkaloid cis‐223B (I) and (.+‐.)‐Xenovenine (II). Issue 11 (18th March 2014) - Barthelme, Alexandre; Richards, David; Mellor, Ian R.; Stockman, Robert A.
Abstract Both the natural alkaloids display the expected neurotoxic properties.